THE MAIN PROBLEMS ENCOUNTERED IN DEVELOPING STUDENTS’ LISTENING AND SPEAKING SKILLS AND THEIR SOLUTIONS - Turegaliyeva, N. (SCIENCE and SOCIETY, 2025)
This article investigates the main problems students encounter when developing listening and speaking skills in English as a foreign language. It focuses on linguistic, semantic, and situational challenges, such as fast-paced speech, unfamiliar vocabulary, poor concentration, and background noise. Drawing on the theoretical works of Underwood, Elukhina, and Borovko, the paper analyzes causes of these difficulties and suggests practical solutions to overcome them. The study also emphasizes the role of motivation, prior knowledge, and phonemic awareness in successful listening comprehension. Special attention is given to learners in multilingual and trilingual environments, where interference from other languages poses an additional barrier. The findings underline the need for methodologically sound strategies and learner-centered instruction to support the development of listening and speaking skills in complex educational contexts.